Comment on "Discrete-time optimal fuzzy controller design global concept approach". - Chonghui Song (IEEE Transactions on fuzzy systems)
In this correspondence, we show that the relationship between the finite optimal trajectory and the infinite optimal trajectory in Lemma 3 of the aforementioned paper cannot act as a theory basis for the further implementation of other theorems and the dynamic decomposition algorithm.